Analisis Kelayakan Penambatan Kapal Floating Storage Regasification Unit (FSRU) di Pelabuhan Kabil, Batam - Heryandri, Kemal; Muhamad Kemal Idris; Khomeiny, Ali Sumara El (Fakultas Teknik Transportasi dan Logistik Trisakti, 2024)
Liquefied Natural Gas (LNG) is an alternative fuel with environmentally friendly solutions. In general, the domestic distribution of natural gas in LNG is more cost-effective than transporting gas through underwater pipelines considering Indonesia as an archipelagic country. However, the current challenge in the LNG industry is the lack of supporting facilities. Storage and regasification facilities are among the infrastructure that requires optimization. Floating Storage and Regasification Unit (FSRU) are viable options for energy distribution that offer opportunities and competitiveness compared to onshore terminals. Small and medium-scale FSRU can serve as an alternative solution due to their relatively fast, flexible, and affordable development process. FSRU is a facility that required fo alternative energy solution fo industry. In principal the FSRU vessel should be moored at the bow and the stern of the vessel for the sake of the stability of the vessel from the waves, tidal currents and winds, therefore not to disrupt the process of the gas production. Surrounding the FSRU vessel should be located the power plant facility and ISO Tank Conk Container Vessel. The viability analysis should be done to evaluate the FSRU Vessel berthing viability in the view of operational and financial at the Port or at the water. Keywords : LNG, FSRU, vessel. berthing, viability